Brachydactyly type A3 may be associated with shorter stature: An observation from a Chinese pediatric sample - Hua-Hong Wu; Ya-Qin Zhang; Cheng-Dong Yu; Fang-Fang Chen; Jun-Ting Liu; Shao-Li Li; Xin-Nan Zong (PLoS ONE, 2025)
Background Brachydactyly type A3 (BDA3), a common finger deformity, demonstrates an inverse epidemiological relationship with population height, suggesting a potential link with individual stature. We aimed to investigate the distribution of BDA3 and its association with shorter stature in Chinese children. Methods From 2022 to 2023, we conducted a cross-sectional survey in 10 randomly selected schools in Beijing with children aged 3–18. We measured height on-site, obtained left hand-wrist X-rays, calculated predicted adult height (PAH) based on height and bone age, and diagnosed BDA3 deformity based on the X-ray images. And we compared the height and PAH between the BDA3 and Non-BDA3 groups by t-test or chi-square test, examined the association of BDA3 with shorter stature and shorter PAH using binary logistic regression model. Results A total of 5,567 children participated, with 573 diagnosed with BDA3 (a detection rate of 10.3%). Notably, girls exhibited a significantly higher detection rate than boys (14.5% vs. 6.3%). The detection rate in children <6 years was twice that in those > 12 years(15.3% vs. 7.6%). The average height and PAH were 0.30 SD and 0.22 SD lower, and the risk of shorter stature and shorter PAH were 1.57 times and 1.47 times higher in the BDA3 group than in the Non-BDA3 group, respectively. And, children >12 years in the BDA3 group had a significantly lower PAH than those in the Non-BDA3 group (about 2.0 cm). Conclusion: Children with BDA3 are more likely to have shorter stature and shorter PAH than those with no BDA3 in Chinese children aged 3–18 years.